2004
DOI: 10.1590/s0074-02762004000100002
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of congenital toxoplasmosis between public and private hospitals from Uberlândia, MG, Brazil

Abstract: The main purpose of the present study was to examine if there is difference in terms of incidence rates of congenital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2005
2005
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
0
9
0
5
Order By: Relevance
“…The infection rate observed in the present study is similar to those in other regions of the country, which ranged between 0.6 and 0.8%, even when different study methods are used. 11,16 Prospective studies by Spalding et al 18 (2003) and Varella et al 1 (2003) in the state of Rio Grande do Sul have reported even higher rates. According to Avelino et al 1 (2003), pregnant women are twice as likely to show seroconversion as are non-pregnant women, and seven times more likely if they are adolescents living in environments contaminated by the feces of host animals.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The infection rate observed in the present study is similar to those in other regions of the country, which ranged between 0.6 and 0.8%, even when different study methods are used. 11,16 Prospective studies by Spalding et al 18 (2003) and Varella et al 1 (2003) in the state of Rio Grande do Sul have reported even higher rates. According to Avelino et al 1 (2003), pregnant women are twice as likely to show seroconversion as are non-pregnant women, and seven times more likely if they are adolescents living in environments contaminated by the feces of host animals.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies 12,16,22 have indicated that therapy can reduce fetal infection in 35 to 60% of cases. Despite the large number of studies over the last three decades, it is still not known whether prenatal treatment of women with presumed toxoplasmosis reduces congenital transmission of T.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some congenital toxoplasmosis studies showed significant differences between the rate of positive diagnosis and the socioeconomic status of some Brazilian regions 14,15 . In addition, it has been observed that some eating habits increase the rate of Toxoplasma gondii transmission.…”
Section: Article/artigomentioning
confidence: 99%
“…As taxas de transmissão congênita e as manifestações clínicas variam de forma acentuada entre os indivíduos com infecção por T. gondii 7 . Neste trabalho evidenciou-se a necessidade de investimento em melhoria de técnicas laboratoriais, a fim de otimizar a assistência às gestantes e filhos expostos, uma vez que a indicação terapêutica pode ser onerosa ao serviço, apesar de saber-se que a utilização de quimioprofilático pode reduzir a transmissão ou as seqüelas ao feto 6 . Há necessidade também de intervir na qualidade das informações obtidas bem como sistematizá-las no sentido de facilitar a tomada de decisões.…”
Section: Comunicação/communicationunclassified